2011
DOI: 10.5688/ajpe75110
|View full text |Cite
|
Sign up to set email alerts
|

Development Needs of Volunteer Pharmacy Practice Preceptors

Abstract: Objective. To determine the training needs and interests of volunteer pharmacy preceptors. Methods. Volunteer preceptors (n5576) were surveyed on various aspects of precepting and their needs related to additional training. Results. Two hundred thirty-six preceptors (40.9%) responded. Preceptors were less confident about enforcing attendance policies, identifying and managing unmotivated or failing students, identifying dishonesty or plagiarism, and handling conflict. While only 29.5% of respondents agreed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
65
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 9 publications
0
65
0
Order By: Relevance
“…9 In one study evaluating the development needs of volunteer pharmacy preceptors, most preceptors (78.4%) indicated that they had previous preceptor training, but 73.5% indicated they would like to have additional training. 10 In another study in which pharmacy student evaluations were compared to preceptor self-evaluations in Thailand, preceptors were found to overrate their performance of key teaching characteristics, such as providing feedback, in comparison with student perceptions. Moreover, all preceptors stated that they did well in giving their students opportunities to ask questions and provide open discussion whereas only 70% of students indicated that their respective preceptors did well in this teaching behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 In one study evaluating the development needs of volunteer pharmacy preceptors, most preceptors (78.4%) indicated that they had previous preceptor training, but 73.5% indicated they would like to have additional training. 10 In another study in which pharmacy student evaluations were compared to preceptor self-evaluations in Thailand, preceptors were found to overrate their performance of key teaching characteristics, such as providing feedback, in comparison with student perceptions. Moreover, all preceptors stated that they did well in giving their students opportunities to ask questions and provide open discussion whereas only 70% of students indicated that their respective preceptors did well in this teaching behavior.…”
Section: Introductionmentioning
confidence: 99%
“…9 Training of preceptors is required by ACPE and encouraged by pharmacy organizations, and studies have shown a benefit from preceptor training and development programs. 10,11 The American Pharmacists Association and the American Society of Health-System Pharmacists, for instance, offer preceptor orientation and training programs to members to improve experiential education, placing emphasis on having qualified preceptors. 12,13 The American Association of Colleges of Pharmacy (AACP) has identified preceptor development as a significant element of quality experiential education, and the need for this training has been identified.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, only two previous studies, conducted in United States 6 and Qatar, 7 have evaluated the preceptors' confidence in their own performance in being a preceptor. Both studies were surveys applying structured Likert-scale statements (3-or 5-point scale).…”
Section: Introductionmentioning
confidence: 99%
“…Both studies were surveys applying structured Likert-scale statements (3-or 5-point scale). [6][7] Some studies have explored pharmacists' attitudes towards being a preceptor, [8][9] and the preceptors' perceptions regarding a new undergraduate pharmacy degree. 10 Tools that support preceptors' work, such as experiential guidelines, 11 the use of the social media by the pharmacy preceptors 12 and the optimal frequency of quality assurance visits in teaching pharmacies 13 have also been studied previously.…”
Section: Introductionmentioning
confidence: 99%
“…The pedagogic design and expected learning outcomes of internships vary in different pharmacy schools and countries, but little is known about the benefits of each system from a pedagogic perspective. 3,[5][6][7][8][9][10][11] Thus, internship curriculum designs are often informed by traditions in pharmacy education rather than by evidence of their pedagogic advantages or effectiveness. 4 In the European Union (EU), higher education practices are harmonized through the Bologna Process signed in 1999.…”
Section: Introductionmentioning
confidence: 99%